2019
DOI: 10.1111/ijpo.12535
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of low‐calorie sweetened beverages is associated with higher total energy and sugar intake among children, NHANES 2011–2016

Abstract: Summary Objective To examine associations between consumption of low‐calorie sweetened beverages (LCSBs), sugar, and total energy intake in children in the United States. Methods We used 24‐hour dietary recalls from 7026 children enrolled in the National Health and Nutrition Examination Survey (NHANES) 2011 to 2016 to assess energy and macronutrient intake among LCSB (≥4 oz LCSB, <4 oz SB), SB (≥4 oz SB, <4 oz LCSB), and LCSB + SB consumers (≥4 oz each) compared with water consumers (≥4 oz water, <4 oz LCSB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…A cross sectional study on 7026 children in the US assessed differences in energy and macronutrient intake between consumers of IS-sweetened beverages, sugar-sweetened beverages or both, compared to water consumers. All three groups of sweetened beverage consumers reported significantly higher energy intake (p < 0.05), and a significantly higher intake of total sugars and added sugars (p < 0.05) [71]. Additionally, a study in 64 Canadian women, which grouped subjects based on regular sweetener intake (both IS and nutritive sweeteners), found that people who regularly consume larger amounts of sweeteners had a significantly greater preference for sweeter beverages (p < 0.05), which correlates with a higher intake of sugar [72].…”
Section: Oral Detection Of Intense Sweetenersmentioning
confidence: 96%
“…A cross sectional study on 7026 children in the US assessed differences in energy and macronutrient intake between consumers of IS-sweetened beverages, sugar-sweetened beverages or both, compared to water consumers. All three groups of sweetened beverage consumers reported significantly higher energy intake (p < 0.05), and a significantly higher intake of total sugars and added sugars (p < 0.05) [71]. Additionally, a study in 64 Canadian women, which grouped subjects based on regular sweetener intake (both IS and nutritive sweeteners), found that people who regularly consume larger amounts of sweeteners had a significantly greater preference for sweeter beverages (p < 0.05), which correlates with a higher intake of sugar [72].…”
Section: Oral Detection Of Intense Sweetenersmentioning
confidence: 96%
“…Drewnowski and Rehm [ 12 ] used a “custom coding algorithm” to identify items containing LCS “based on their description, energy density (kcal/100 g), and total and added sugars content (g) per average consumption report;” they did not provide specific information about the values used for their energy or sugar criteria or report the number of foodcodes or their identities. In two recent publications [ 7 , 21 ], we identified foodcodes as LCSBs if the FNNDS main foodcode description contained terms associated with low-calorie sweeteners, such as “diet”, “dietetic”, “low-calorie”, “no sugar added”, “light or lite”, “sugar-free”, “sugar substitute”, “low-calorie sweetener”, “no-calorie sweetener”, “reduced sugar”, “less sugar”, “zero calorie”, or “no sugar added.” For cycles spanning 2009–2012, this approach identified a total of 136 LCSB foodcodes [ 21 ], with 148 LCSB foodcodes identified for NHANES cycles 2011–2016 [ 7 ], although we also did not report the number or the identity of those foodcodes in those publications. In addition to the wide variance in the number of foodcodes identified as LCSBs, like caloric density-based approaches, text-based approaches can incorrectly identify foodcodes as LCSBs when they do not in fact contain any LCS.…”
Section: Phasementioning
confidence: 99%
“…We hypothesized that there would be broad heterogeneity in the approaches used to identify and categorize LCSBs, and that the number of beverages classified within beverage groups would vary substantially across studies, potentially leading to widespread misclassification of sweetened beverages. We also aimed to provide an example of how changing beverage foodcode classifications and correcting errors in WWEIA/NHANES can affect the outcomes of analyses, by re-analyzing previously published findings [ 7 ] from our group. We conducted this study in three separate phases.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, the consumption of artificially sweetened soft drinks was associated with an increased risk of death from cardiovascular disease [83]. Children who consumed artificially sweetened beverages consumed more calories than children who drank sugar-sweetened beverages [84]. There are also concerns that non-nutritive sweeteners may also alter the gut microbiota and increase obesity-associated inflammation and innate and cell-mediated immunity [85].…”
Section: Diet Sodamentioning
confidence: 99%